2020
DOI: 10.1002/bmc.4799
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis of round and elongated spermatids during spermiogenesis in mice

Abstract: Spermiogenesis in mammals is an exclusive process during which haploid round spermatids mature into spermatozoa in the testis. Any abnormality in the process of spermiogenesis may result in male infertility. The aim of the present study was to characterize the differentially expressed proteins between round and elongated spermatids in mice using label‐free quantitative mass spectrometry. Of the 2411 proteins identified in this study, 333 were differentially expressed with a ≥10‐fold change, including 208 upreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Terms related to mRNA processing and DNA replication were kept in the meiotic zone (continuum B) but completed by a chromosome-related process in accordance with meiosis (i.e., nuclear chromosome segregation and the meiotic cell cycle in biological processes; chromosomal region and condensed chromosome in cellular component; homologous recombination and mismatch repair in the wiki pathway). Interestingly, biological processes related to methylation and histone modifications were also retrieved, which could be associated with the establishment of a specific regulation of gene expression during spermatogenesis. Sphingolipid metabolism was also noticed in wiki pathway and this could be related to male meiotic cytokinesis. , Estrogen signaling was also highlighted, which is in agreement with one of the pioneering works of G. V. Callard on the paracrine function of estrogens during spermatogenesis in a shark species . Proteins associated with spermiogenesis (continuum C and zone D) were unsurprisingly related to the spermatid flagellum development (i.e., for continuum C: cilium organization in biological process; cilium in cellular component; dynein in molecular function) and completed by cilium activity (i.e., for zone D: motile cilium in cellular component; calmodulin and magnesium binding in molecular function; mitochondrial protein import in the reactome pathway and purine metabolism in the wiki pathway).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Terms related to mRNA processing and DNA replication were kept in the meiotic zone (continuum B) but completed by a chromosome-related process in accordance with meiosis (i.e., nuclear chromosome segregation and the meiotic cell cycle in biological processes; chromosomal region and condensed chromosome in cellular component; homologous recombination and mismatch repair in the wiki pathway). Interestingly, biological processes related to methylation and histone modifications were also retrieved, which could be associated with the establishment of a specific regulation of gene expression during spermatogenesis. Sphingolipid metabolism was also noticed in wiki pathway and this could be related to male meiotic cytokinesis. , Estrogen signaling was also highlighted, which is in agreement with one of the pioneering works of G. V. Callard on the paracrine function of estrogens during spermatogenesis in a shark species . Proteins associated with spermiogenesis (continuum C and zone D) were unsurprisingly related to the spermatid flagellum development (i.e., for continuum C: cilium organization in biological process; cilium in cellular component; dynein in molecular function) and completed by cilium activity (i.e., for zone D: motile cilium in cellular component; calmodulin and magnesium binding in molecular function; mitochondrial protein import in the reactome pathway and purine metabolism in the wiki pathway).…”
Section: Resultssupporting
confidence: 71%
“…Thirty-one ubiquitin-conjugating enzymes were found with a higher abundance of 11 in zone A, 4 identified only in zone A, and 7 in the zones C and/or D. UBE2G2 and UBE4B were the only two enzymes showing higher abundance in zone B corresponding to cysts with spermatocytes. Their role during spermatogenesis has been little studied, with the exception of publications showing differences in levels of UBE2G2 in subfertile men and overexpression of UBE4b in elongated spermatids in mice . Relatively few E3 ubiquitin ligases were found in the present study, while many isoforms are expressed in the testis. , Of the E3 substrates identified, CUL3 was most abundant in the spermatid zones, which is in agreement with its previously reported profile in mice, while CUL2 appeared to be most abundant only in the early spermatid zone, although its expression has been reported to regulate meiotic entry in the C.…”
Section: Resultsmentioning
confidence: 99%
“…Early male gametocytes (day 4 – stage II/III) showed highest expression of 579 genes (118 (20%) of unknown function). The predominant processes were related to proteolysis and proteasome complex, consistent with the critical function of proteostasis during metazoan spermatogenesis [ 67 , 68 ]. In the intermediate male gametocytes (day 6 stage III/IV), 694 genes (224 (32%) of unknown function), were found to be highest expressed.…”
Section: Resultsmentioning
confidence: 89%
“…Dramatic morphological changes will occur during spermiogenesis, transforming round spermatids into elongated, tadpole-like spermatozoa with only one-fifth of their original sizes [3]. Thousands of germ cell-specific genes are highly expressed in haploid germ cells and participate in spermiogenesis [4,5]. In the past 15 years, gene knockout studies have identified 20 male germ cell specific genes or gene subtypes that play a crucial role in spermatogenesis [6].…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, the oocyte is characterized by rich microvilli on the membrane surface [7]. Sperm-oocyte binding and fusion mainly occurs in this area, emphasizing its importance for fertilization [4].…”
Section: Introductionmentioning
confidence: 99%